MARS UMPSA recognises students and alumni leadership character - Siti Nur Azwin, Zulkapri (UMPSA, 2024)
KUANTAN, 18 May 2024 - The Mercu Sanjung Award (MARS) Ceremony, Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) recognises students who have shown holistic and competent leadership in line with strategic initiatives to produce holistic graduates.